Residual stresses in multi-layered silicon-on-sapphire thin film systems - Pramanik, Alokesh; Zhang, Liangchi (Elsevier, 2011)
This paper uses the finite element method to analyse the generation and evolution of residual stress in silicon-on-sapphire thin film systems during cooling. The effects of material properties, thin film structures and processing conditions, on the stress distribution were explored in detail. It was found that under certain conditions, significant stress concentration and discontinuity can take place to initiate crack and/or delamination in the systems. However, these can be minimised by controlling the buffer layer thickness.